2020
DOI: 10.1002/per.2229
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and the Big Five Personality Traits: A Meta–Analysis

Abstract: total n = 93 668) addressed how the Big Five dimensions of personality (extraversion, agreeableness, conscientiousness, neuroticism, and openness) are related to loneliness. Robust variance estimation accounting for the dependency of effect sizes was used to compute meta-analytic bivariate correlations between loneliness and personality. Extraversion (r = À.370), agreeableness (r = À.243), conscientiousness (r = À.202), and openness (r = À.107) were negatively related to loneliness. Neuroticism (r = .358) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
215
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(249 citation statements)
references
References 176 publications
25
215
2
7
Order By: Relevance
“…One possible interpretation-assuming a causal relation between personality and wellbeing-is that extraversion loses some of its protective value for mental health during phases of drastic and imposed public and social life restrictions. This is in line with previous research suggesting that extraverts have higher well-being because they seek the company of others, engage in social activities, and interact with others for support (Buecker et al 2020)activities which became temporarily less available both in private life (meeting friends and family) and in the work context (talking to colleagues). Consequently, extraverts may have felt more burdened and lonelier than usual, decreasing the overall association between extraversion and psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…One possible interpretation-assuming a causal relation between personality and wellbeing-is that extraversion loses some of its protective value for mental health during phases of drastic and imposed public and social life restrictions. This is in line with previous research suggesting that extraverts have higher well-being because they seek the company of others, engage in social activities, and interact with others for support (Buecker et al 2020)activities which became temporarily less available both in private life (meeting friends and family) and in the work context (talking to colleagues). Consequently, extraverts may have felt more burdened and lonelier than usual, decreasing the overall association between extraversion and psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in contrast to the high negative meta-analytic correlation between extraversion and loneliness even after controlling for other personality traits (Buecker et al 2020) and the moderate to high positive meta-analytic correlation between extraversion and well-being (Steel et al 2008;DeNeve and Cooper 1998). However, they are compatible with a recent Covid-19 study in which higher extraversion was related to greater health-and economy-related concerns during the pandemic (Aschwanden et al 2020).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Results are in accordance with a cross-sectional study showing that both communion and agency were related to lower levels of loneliness (Zarbatany et al, 2004). The results are also in line with empirical research on similar personality constructs of social relevance, such as agreeableness and extraversion, where similar cross-sectional relationships with loneliness were found (Buecker, Maes, Denissen, & Luhmann, 2020).…”
Section: Predictors Of Loneliness Trajectories Across Adolescence Andsupporting
confidence: 90%
“…Previous experiences of loneliness may be one predictor which leads to a cyclical pattern of behaviors which results in additional feelings of loneliness over time ( Cacioppo and Hawkley, 2009 ). Personality influences social relationships and these relatively fixed characteristics may contribute to the cycle of loneliness, particularly characteristics indicating neuroticism ( Buecker et al., 2020 ). Nonetheless, other research has found that levels of neuroticism decrease over the life course ( Ormel et al., 2012 ), which is promising as older adults who experience elevated levels of neuroticism earlier in the life course may be able to seek and maintain the relationships they desire in order to reduce loneliness.…”
Section: Differing Dimensions Based On Social Relationsmentioning
confidence: 99%